The Immune System and Its Ecology. - Tauber, Alfred I. (Philosophy of Science, 2008)
In biology, the 'ecological orientation' rests on a commitment to examining systems, and the conceptual challenge of defining that system now employs techniques and concepts adapted from diverse disciplines (i.e., systems philosophy, cybernetics, information theory, computer science) that are applied to biological simulations and model building. Immunology has joined these efforts, and the question posed here is whether the discipline will remain committed to its theoretical concerns framed by the notions of protecting an insular self, an entity demarcated from its environment, or will shift its focus of interest to a wider context. An ecological perspective emphasizes the interchange between the organism and its environment, the processing of information, and the regulation arising from responses to this larger context. Moving from the first attempts at modeling the immune system as a closed network, immunologists have joined the general interest in systems analysis, and that move might portend a significant shift to an open, more holistic consideration of immune regulation.